2007
DOI: 10.1542/peds.2006-2966
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation in the “Gray Zone” of Viability: Determining Physician Preferences and Predicting Infant Outcomes

Abstract: The "gray zone" for delivery room resuscitation seems to be between 500 and 600 g and 23 and 24 weeks. For infants born in that zone, neonatologists' reliance on accurate prediction of death or morbidity in the delivery room may be misplaced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
123
1
17

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(143 citation statements)
references
References 18 publications
2
123
1
17
Order By: Relevance
“…6,8,[14][15][16][17] Importantly, these data have not changed substantially over the past 10 to 15 years. [8][9][10][11][12] In an earlier study, although approximately 10% of neonates born at 22 weeks' gestation survived to admission to the NICU, none of them were alive by 6 months of age. 18 In more recent studies, none of the infants born at <23 weeks were reported to survive to discharge from the NICU.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…6,8,[14][15][16][17] Importantly, these data have not changed substantially over the past 10 to 15 years. [8][9][10][11][12] In an earlier study, although approximately 10% of neonates born at 22 weeks' gestation survived to admission to the NICU, none of them were alive by 6 months of age. 18 In more recent studies, none of the infants born at <23 weeks were reported to survive to discharge from the NICU.…”
Section: Resultsmentioning
confidence: 96%
“…12 Below the lower limit of the 'gray zone,' the infant is too immature to have any reasonable chance for survival without severe deficits. For these infants, provision of care other than comfort care is unreasonable.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations